Co-Creating Energy Models in Africa: Stakeholder Perspectives from Morocco, Mozambique, and Mali - Matak, Nikola; Krajacic, Goran; Rajlic, Ven; Diarra, Charles; Ballo, Abdoulaye; Tsamba, Alberto Julio; Cuamba, Boaventura Chongo; Zahboune, Hassan (International Journal of Sustainable Energy Planning and Management, 2025)
Stakeholder engagement, data collection, and more importantly, the analysis of the collected data and their implementation are critical components for an effective energy system modelling. The energy modelling needs to also address local specificizes as in this case focused on African continent these needs to include specific energy challenges, such as inadequate access to electricity, unreliable energy supply coupled with a heavy reliance on traditional biomass. Stakeholder views on the energy modelling process within the three African regions with specific case studies in Morocco, Mozambique and the Niger river basin in Mali are investigated. To effectively capture the diverse and multifaceted viewpoints of stakeholders, a mixed-methods approach was employed, combining surveys with interviews and focus group discussions. The stakeholders included through Quadruple helix approach are representing academia & research institutions, civil society, policy makers and investors in the mentioned countries. The objectives of the research were to understand energy needs and priorities in different countries, assess current practices when it comes to energy modelling, facilitate collaboration between different stakeholders, and gather insights for development of energy models.